Characterizing Primary Care Visit Activities at Veterans Health Administration Clinics1. Issue 1 (January 2015) - Gutierrez, Jennifer C.; Terwiesch, Christian; Pettit, Amy R.; Marcus, Steven C.
Abstract : EXECUTIVE SUMMARY : Medical home models seek to increase efficiency and maximize the use of resources by ensuring that all care team members work at the top of their licenses. We sought to break down primary care office visits into measurable activities to better understand how primary care providers (PCPs) currently spend visit time and to provide insight into potential opportunities for revision or redistribution of healthcare tasks. We videotaped 27 PCPs during office visits with 121 patients at four Veterans Health Administration medical centers. Based on patterns emerging from the data, we identified a taxonomy of 12 provider activity categories that enabled us to quantify the frequency and duration of activities occurring during routine primary care visits. We conducted descriptive and multivariate analyses to examine associations between visit characteristics and provider and clinic characteristics. We found that PCPs spent the greatest percentage of their visit time discussing existing conditions (20%), discussing new conditions (18%), record keeping (13%), and examining patients (13%). Providers spent the smallest percentage of time on preventive care and coordination of care. Mean visit length was 22.9 minutes (range 7.9‐58.0 minutes). Site‐level ratings of medical home implementation were not associated with differences in how visit time was spent. These data provide a window into how PCPs are spending face‐to‐face time with patients. The methodology and taxonomy presented here may prove useful for future quality improvement and research endeavors, particularly those focused on opportunities to increase nonappointment care and to ensure that team members work at the top of their skill level.